PENGARUH EUTROFIKASI TERHADAP KUALITAS AIR DI SUNGAI JENEBERANG - Alfionita, Andi Nur Afia; Patang, Patang; Kaseng, Ernawati S (Universitas Negeri Makassar, 2019)
The river is one of the natural resources that are beneficial to human life, such as in agriculture and aquaculture processes, particulary in the Jeneberang River. Along the Jeneberang River flow, be found a rice fields area, mining and resident settlements which causes the entry of organic matter into river flow bodies. The purpose of this study was to determine the level of eurofication that occurred in the Jeneberang River and also to determine the effect of eutrophication on water quality in that river. This research was descriptive research using survey methods, this research was carried out by taking water samples at five stations namely, upstream, middle and downstream. The results showed that eutrophication had occurred in the Jenebrang River and was at the hypertrophic status. In addition, the results of the regression test showed that eutrophication hadÂ a significant take effect on dissolved oxygen content and Ph on the Jeneberang river. However, eutrophication does no significant effect on abundance Â plankton, and temperature.